Comprehensive Framework for Collaborative Decision-Making in Evaluating Computer Network Security Using Interval Neutrosophic Information - Wenbao Qiao (Neutrosophic Sets and Systems)
Computer network security (CNS) evaluation is crucial for protecting information assets and maintaining the stable operation of network systems. Through this evaluation, potential threats and vulnerabilities within the network can be systematically identified, effectively preventing possible cyber-attacks and data breaches. Additionally, network security evaluation helps enterprises and organizations allocate security resources appropriately, enhancing their ability to respond to emergencies and ensuring business continuity and data integrity. In summary, network security evaluation is one of the foundational tasks for achieving continuous, secure, and stable network operations. The CNS evaluation is multiple-attribute group decision making (MAGDM). Then, the generalized TODIM(GTODIM) approach has been developed to deal with MAGDM. The interval neutrosophic sets (INSs) are defined as an effective tool for representing uncertain data during the CNS evaluation. In this manuscript, the interval neutrosophic number generalized TODIM (INN-GTODIM) approach is proposed to put forward the MAGDM under INSs. Finally, numerical example study for CNS evaluation is introduced to validate the INN-GTODIM approach. The primary contributions of this study are outlined: (1) Deriving weight information through the application of average method, enhancing the robustness of the decision-making process; (1) Implementing the INN-GTODIM approach for MAGDM scenarios that utilize INSs, showcasing its adaptability to complex decision-making environments; (1) Applying the INN-GTODIM approach specifically to the domain of CNS evaluation, and comparing its performance against existing approaches to highlight its strengths and improvements; (4) Providing a detailed comparative analysis, which clearly demonstrates that the INN-GTODIM approach significantly enhances the effectiveness of CNS evaluations.